Pengenalan Akuntansi Berbasis SAK EMKM Sebagai Kelayakan Usaha dan Peningkatan Kapasitas Pelaku UMKM di Banjarmasin - Monica Rahardian Ary Helmina; Alfian Alfian; Meina Wulansari Yusniar; Mellani Yuliastina (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
Micro, Small and Medium Enterprises (MSMEs) at South Kalimantanare a positive contributor to economic growth. It was noted that this year the role of MSMEs reached up to 98%. Based on data for 2020 the number of MSMEs in South Kalimantan has reached more than 33,700. By absorbing a workforce of up to 60,000 people. Credit disbursement is planned to develop MSMEs. One of the requirements for applying for additional capital for a business is a financial report. UMKM Sukses Banua is a community of micro, small and medium enterprises that houses creative entrepreneurs. Members numbered more than 200 members. MSME actors who are members of this association have not kept records or bookkeeping that refer to SAK EMKM-based accounting.The goal to be achieved in this program is to develop the skills of MSME traders or actors so that they have the ability to make SAK EMKM - based accounting practices that will be applied to their businesses, so it is hoped that these MSME actors can have an understanding of the financial position of their businesses and improve their business performance based on financial reports. his efforts. The method used in implementing an understanding of accounting based on SAK EMKM is Participatory Based Learning, namely involvement in the planning, implementation, monitoring and evaluation stages of programs / activities by the proposing team. At the end of the program partners are able to understand bookkeeping, recording and financial reporting in accordance with SAK EMKM - based accounting standards. In the end, with the existence of these financial reporting standards, of course, they can become a simple reference and are more easily accepted by a wider circle of entrepreneurs.